ANALISIS PARAMETER TENSION TERHADAP KUALITAS LAMINASI PADA MESIN DRY LAMINASI - Ahmad Irza Nugroho, Ahmad Irza Nugroho (Kreator, 2025)
In the flexible packaging industry, the quality of lamination results significantly affects both the appeal and protective function of the product. One common issue in the dry lamination process is lamination wrinkle defects, which can reduce the packaging quality standards. This study aims to analyze the effect of variations in tension parameters in the dry lamination machine—specifically the tension in Unwinder 1, Unwinder 2, and the Laminator—on the print quality of snack packaging. The research was conducted using a quantitative experimental approach at PT XXX, involving 64 samples with varied tension settings and quality testing through laboratory tests (sealing strength, bonding strength, and dry glue) as well as visual inspections. The Pearson correlation test results indicated a weak to very weak relationship between tension parameters and laboratory test outcomes. The Kruskal-Wallis non-parametric test showed no significant differences in lamination quality based on tension variation. However, the Spearman correlation test for visual defects revealed a strong correlation between Laminator tension and the occurrence of lamination wrinkles and shrinkage patterns. Therefore, controlling the tension parameters—especially at the Laminator—is essential in reducing visual defects during the dry lamination process.